Mittelalterforschung als gesellschaftliche und interdisziplinäre Herausforderung Zukunftsperspektiven des Mediävistenverbandes - mit einem Rückblick auf seine Geschichte - Drews, Wolfram 1966- (Das Mittelalter, 2021)
The introduction addresses ways to secure the future of medieval studies, outlining social and academic challenges faced by scholars in their respective fields, as well as in their efforts to foster interdisciplinary cooperation. Three successive steps are made to introduce the six interdisciplinary strategic papers as well as the 18 disciplinary papers included in the volume, which present individual subjects. First, the editors highlight the current social challenges, which have meant that medieval studies are no longer taken for granted. Medievalists are therefore called upon to prove and defend the relevance of their subjects. Afterwards, we look back at the history of our professional organization, highlighting new developments which have characterized medieval studies since the turn of the millennium. Such new trends have contributed to an ever keener awareness of current challenges that need to be faced in order to secure the future of medieval studies. Finally, we present the outline of this issue of our journal, pinpointing links between the papers representing individual disciplines, thereby outlining challenges as well as prospects for medieval studies.